Socialization of Tokka Nature Tourism MSMEs in Maros Regency - Petrus Petrus; Nurmillah Nurmillah; Arga Arga; Muh. Darwis Nur Tinri; Suwardi Suwardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pejuang Republik Indonesia, 2026)
This community service aims to increase awareness and capacity of MSME actors in developing the Tokka natural tourism sector in Maros Regency, South Sulawesi. Tokka natural tourism has great potential as an ecotourism destination with distinctive karst natural beauty, natural caves, and high biodiversity. However, this potential has not been optimally utilized by local communities, especially MSME actors engaged in the tourism sector. The method used in this service is a participatory approach through socialization, training, and mentoring to local MSME actors. The activity was carried out involving the Maros Regency Tourism Office, local tourism communities, and academics from the Islamic University of Makassar. The results of the service show that after participating in the socialization program, MSME actors have a better understanding of the importance of digital-based tourism promotion, local product packaging, and environmentally friendly services. In addition, this activity also encourages collaboration among MSME actors to create integrated tourism packages that combine culinary, handicrafts, and local tour guide services. This program is expected to increase tourist visits, create new jobs, and improve the economic welfare of communities around the Tokka tourism area.